Type 2 diabetes mellitus related sarcopenia: a type of muscle loss distinct from sarcopenia and disuse muscle atrophy - Liu, Zhenchao; Guo, Yunliang; Zheng, Chongwen (Frontiers in Endocrinology, 2024)
Muscle loss is a significant health concern, particularly with the increasing trend of population aging, and sarcopenia has emerged as a common pathological process of muscle loss in the elderly. Currently, there has been significant progress in the research on sarcopenia, including in-depth analysis of the mechanisms underlying sarcopenia caused by aging and the development of corresponding diagnostic criteria, forming a relatively complete system. However, as research on sarcopenia progresses, the concept of secondary sarcopenia has also been proposed. Due to the incomplete understanding of muscle loss caused by chronic diseases, there are various limitations in epidemiological, basic, and clinical research. As a result, a comprehensive concept and diagnostic system have not yet been established, which greatly hinders the prevention and treatment of the disease. This review focuses on Type 2 Diabetes Mellitus (T2DM)-related sarcopenia, comparing its similarities and differences with sarcopenia and disuse muscle atrophy.The review show significant differences between the three muscle-related issues in terms of pathological changes, epidemiology and clinical manifestations, etiology, and preventive and therapeutic strategies. Unlike sarcopenia, T2DM-related sarcopenia is characterized by a reduction in type I fibers, and it differs from disuse muscle atrophy as well. The mechanism involving insulin resistance, inflammatory status, and oxidative stress remains unclear. Therefore, future research should further explore the etiology, disease progression, and prognosis of T2DM-related sarcopenia, and develop targeted diagnostic criteria and effective preventive and therapeutic strategies to better address the muscle-related issues faced by T2DM patients and improve their quality of life and overall health.